Do changes in neuromuscular activation contribute to the knee extensor angle-torque relationship? - Lanza, M. B.; Balshaw, T. G.; Folland, J. P. (Frontiers in Physiology, 2017)
The influence of joint angle on knee extensor neuromuscular activation is unclear due in part due to the diversity of surface electromyography (sEMG) and/or interpolated twitch technique (ITT) methods employed. The aim of the study was to compare neuromuscular activation, using rigorous contemporary sEMG and ITT procedures, during isometric maximal voluntary contractions (iMVC) of the quadriceps femoris (Q) at different knee-joint angles and examine if activation contributes to the angle-torque relationship. Sixteen healthy active males completed two familiarization sessions and two experimental sessions of isometric knee extension and knee flexion contractions. The experimental sessions included the following at each of four joint angles (25°, 50°, 80° and 106°): iMVCs (with and without superimposed evoked doublets); submaximal contractions with superimposed doublets; evoked twitch and doublet contractions whilst voluntarily passive and knee flexion iMVC at the same knee joint positions. Absolute Q EMG was normalised to MMAX peak-to-peak amplitude and the doublet-voluntary torque relationship was used to calculate activation with the ITT (ACTITT). Agonist activation, assessed with both normalised EMG and ACTITT, was reduced in the more extended compared to the more flexed positions (25 & 50 vs. 80 & 106°; P = 0.016), whereas antagonist co-activation was greatest in the most flexed compared to the extended positions (106 vs. 25 & 50°; P = 0.02). In conclusion, both agonist and antagonist activation differed with knee joint angle during knee extension iMVCs and thus both likely contribute to the knee extensor angle-torque relationship.